Laparoscopic appendectomy and cholecystectomy in a 2-year-old with acute suppurative appendicitis and gallbladder torsion: a case report - Sun, Jian; Zhang, You-Cheng; Gu, Chun-Hui (Frontiers in Pediatrics, 2025)
BackgroundPediatric gallbladder torsion is a rare but potentially life-threatening cause of acute abdomen. The first case was reported in the 19th century, yet the precise pathogenesis remains unclear. Due to its nonspecific symptoms, gallbladder torsion in children is frequently misdiagnosed as more common conditions, such as acute appendicitis, cholecystitis, or gastrointestinal infections.Case presentationA 2-year and 4-month-old boy was admitted to our emergency department with abdominal pain, fever, and vomiting. Initial blood tests revealed a white blood cell count of 13.13 × 109/L, neutrophil percentage at 76.1%, and an absolute neutrophil count of 9.99 × 109/L. Abdominal CT indicated thickened gallbladder walls, a partially blurred appendix margin, an intraluminal dense shadow, and multiple enlarged lymph nodes, along with pelvic effusion. A diagnosis of acute appendicitis was made. Emergency laparoscopy showed a suppurative appendix, leading to an appendectomy. Further inspection revealed a 360° counterclockwise torsion of the gallbladder neck with necrosis and black discoloration, without perforation. A laparoscopic cholecystectomy was performed. Nine days postoperatively, the child developed symptoms of an upper respiratory tract infection, necessitating transfer to the pediatric respiratory department, and was discharged on postoperative day 19 with no complications.ConclusionLaparoscopic exploration for pediatric acute appendicitis should include the gallbladder as a standard investigation target.